Drivers of training participation in low skilled jobs: the role of `voice', technology, innovation and labor shortages in German companies - Philip Wotschack (International Journal of Training and Development, 2020)
This article investigates the role of `voice', technology, innovation (of products, services, or processes) and labor shortages in the training participation of low skilled workers in German companies. By building on the key findings of previous research, hypotheses on drivers of training participation are derived from filter theory and the concept of social embeddedness. Regression and cluster analysis based on the German IAB Establishment Panel (wave 2011) show evidence that training participation is shaped by `voice'-related institutional company characteristics such as employee representation or formalized HR practices. Both characteristics often cluster together. Regression analyses confirm that companies in this cluster train a higher share of their low-skilled workforce. The share is particularly high when companies in this cluster face labor shortages. Apart from that, advanced technology and recent innovations at the company level are not related to higher rates of training participation among low skilled workers.
Keywords: 300